Menjaga Iman Islam di Tengah Tantangan Dunia Modern - Edinda Juwita; Farhan Ramadhan; Rifki Putra Pratama; Najwa Ayu Risma; Wismanto Wismanto; Fitria Mayasari (Journal of Student Research, 2025)
The background of this study is the significance of faith for Muslims in facing the challenges of the modern era, amidst the rapid development of technology and open access to information that often impacts the quality of faith. The purpose of this study is to analyze the role of faith in maintaining inner peace and mental well-being for Muslims, as well as to provide recommendations for strengthening faith in the digital age. The method used is a qualitative approach with in-depth interviews and questionnaires conducted with Muslims from various backgrounds. The results show that individuals with strong faith are more capable of handling social pressures and upholding Islamic values, even though social media can be a negative influence.